Whither Synodality in India? Acceptance and Resistance Towards Being A Synodal Church in India - Karunanidhi, Yesu (Asian Horizons, 2024)
This article explores the concept of synodality within the context of the Catholic Church in India, focusing on both its acceptance and resistance. Synodality, emphasizing communal discernment and collaborative decision-making, reflects the Church’s mission to journey together. The article examines the theological and cultural factors contributing to the embrace of synodality among Indian Catholics, highlighting successful instances of synodal practices. Conversely, it addresses the challenges and resistance faced, including hierarchical structures, cultural diversity, and socio-political dynamics. Through a balanced analysis, this study aims to provide insights into the future trajectory of synodality in India, offering recommendations for fostering a more inclusive and participatory Church.